The teacher and its social role - doi:10.5020/18061230.2004.p206 - Irineu Lima de Albuquerque (Universidade de Fortaleza, 2012)
The teacher / student interaction is based on a professional and human interrelation, founded on respect and ethics and on the understanding that the student is not a passive subject in the process of learning. He / she brings a range of knowledge and allows a mutual exchange of practices by means of which the teacher builds his / her intellect dayby- day. This study aims at emphasizing the relevant points within this interrelation as well as the teacher social role. The teacher constitutes the cross beam in the process of building the student's character, a process that must be developed by means of a combined experimentation. The educational activities, for their turn, must be centered in the students' abilities, expectations, interests, opportunities, possibilities and learning conditions. Motivation is the teaching and learning master spring in order to achieve the main objectives in education that are the sedimentation of the previous knowledge, the correction of the distortions and the acquisition of new knowledge.